2018
DOI: 10.1108/mrr-03-2017-0092
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and firm performance: the mediating role of functional performances

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
131
0
25

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(169 citation statements)
references
References 78 publications
(146 reference statements)
13
131
0
25
Order By: Relevance
“…That is way entrepreneurial orientation does not have a positive effect on marketing performance. However, this is inversely proportional to the research conducted by Rezaei and Ortt (2018). The study revealed that entrepreneurial orientation had a positive and significant effect on marketing performance.…”
Section: H4: Entrepreneurial Orientation Has a Positive Effect On Commentioning
confidence: 83%
See 1 more Smart Citation
“…That is way entrepreneurial orientation does not have a positive effect on marketing performance. However, this is inversely proportional to the research conducted by Rezaei and Ortt (2018). The study revealed that entrepreneurial orientation had a positive and significant effect on marketing performance.…”
Section: H4: Entrepreneurial Orientation Has a Positive Effect On Commentioning
confidence: 83%
“…stated that marketing performance could be obtained from the application of ERP (Enterprise Resource Planning) through competitive advantage. Apart from implementing ERP in the enterprise, marketing performance and competitive advantage could also be obtained from the existence of entrepreneurial orientation (Rezaei and Ortt, 2018). Another variable that can affect marketing performance and competitive advantage is the presence of an effective distribution channel (Kuswantoro, et al 2012).…”
Section: A Critical Success Factorsmentioning
confidence: 99%
“…Orientasi kewirausahaan secara tidak langsung mempengaruhi kinerja perusahaan dalam menciptakan pengetahuan (Li, Huang, & Tsai, 2009). Keberhasilan sebuah perusahaan membutuhkan pengetahuan tentang kewirausahaan yang lebih untuk mencapai kinerja perusahaan yang unggul (Rezaei & Ortt, 2018). Dengan demikian, proses menciptakan pengetahuan memainkan peranan penting dalam mediasi dimana orientasi kewirausahaan bermanfaat bagi kinerja perusahaan.…”
Section: Eo Dan Kinerja Perusahaanunclassified
“…Hal tersebut dikarenakan kekuatan manajerial merupakan komponen penting dalam menentukan keberhasilan orientasi kewirausahaan. Terdapat efek yang berbeda pada fungsi perusahaan yang dapat membentuk nilai internal untuk menentukan kinerja perusahaan (Rezaei & Ortt, 2018). Untuk mencapai kinerja yang unggul, perusahaan perlu menerapkan orientasi kewirausahaan melalui kapabilitas pemasaran (Sok, Snell, Lee, & Sok, 2017).…”
Section: Eo Dan Kinerja Perusahaanunclassified
“…Perusahaan secara keseluruhan berhubungan positif dengan kinerja perusahaan terlepas dari jenis ukuran kinerja dan konteks industry (Lee & Roh, 2012) Orientasi kewirausahaan (EO) merupakan faktor penting untuk kelangsungan hidup, profitabilitas, dan pertumbuhan perusahaan (Dess, Pinkham, & Yang, 2011). Telah ditemukan dalam banyak studi berbeda bahwa EO memiliki efek positif pada kinerja perusahaan (Rezaei & Ortt, 2018). EO mengacu pada proses pembuatan strategi yang memandu perusahaan untuk mengembangkan inovasi konstan, mengadopsi postur proaktif di pasar dan melakukan investasi berisiko (Shirokova, Bogatyreva, Beliaeva, & Puffer, 2016) Di lain pihak, perusahaan dengan orientasi kewirausahaan yang tinggi bisa saja mengalami kinerja yang buruk.…”
Section: Orientasi Kewirausahaan Dalam Turbulensi Lingkungan Bisnis Kunclassified